TINJAUAN YURIDIS KEGIATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DI JAKARTA PUSAT (STUDI DI KELURAHAN KEMAYORAN) : Juridical Review of Complete Systematic Land Registration Activities in Central Jakarta (Study in Kelurahan Kemayoran) - Azka Hady Suryajaya; Novina Sri Indiraharti (Faculty of Law, Universitas Trisakti, 2024)
Complete systematic land registration (PTSL) in Central Jakarta has been started since 2017 with target of 4.000 plots land, covering 11 Kelurahan, including Kemayoran Kelurahan. The formulation the problem in this study is 1) Are PTSL activities in Kemayoran village in accordance with the provisions of applicable laws and regulations? 2) What are the legal obstacles that occur in the implementation of PTSL activities in Kemayoran sub-district and how can legal solutions be carried out there are legal obstacles? The research method used in study uses normative legal research, with descriptive secondary data, which is analyzed qualitatively using deductive conclusions. The results and conclusions this study are PTSL activities in Kemayoran village accordance with PP No. 24 of 1997 and PMNA No. 3 of 1997, but in the provisions regarding conversion of registered land plots, old land rights that should be with property rights, are only converted into HGB stipulated in Article 26 letter A of ATR/BPN Ministerial Regulation No. 6 of 2018. The legal obstacle that occurs to citizens is lack of files. Legal settlement can done by making statement letter physical control land parcels and people who have not paid BPHTB and Income Tax can make statement letter.